Cranial-first approach of laparoscopic left colectomy for T4 descending colon cancer invading the Gerota’s fascia - Atsushi Ogura; Ryutaro Kobayashi; Satoru Kawai; Kenji Takagi; Kiyotaka Kawai; Takashi Maeda; Tsukasa Aritake; Natsuki Nagano; Satoaki Kamiya (Surgical Case Reports, 2019)
Abstract Background The safety and feasibility of laparoscopic colectomy for T4 colorectal cancer remain controversial. We believe that setting a “Goal” that will guide the surgeons in returning from the deep layer could be the key to safe en bloc resection of neighboring organs. For descending colon cancer, the cranial-first approach makes it possible to clearly visualize the pancreas and origin of the transverse mesocolon, leading to safe splenic flexure mobilization and complete mesocolic excision, which is the strongest advantage of this approach. Case presentation A 75-year-old woman was diagnosed with T4 descending colon cancer invading the Gerota’s fascia. We performed laparoscopic left colectomy using the cranial-first approach to set a “Goal” at the inferior border of the pancreas for safe resection of the Gerota’s fascia. The total operative time was 233 min, and the estimated blood loss was 98 ml. She was discharged after surgery without postoperative complications. Pathological findings revealed the invasion into the Gerota’s fascia, and the resection margin was negative for cancer. Conclusions The cranial-first approach of laparoscopic left colectomy appears to be safe and feasible and could be a promising method for selected patients with T4 descending colon cancer invading the Gerota’s fascia.